Pemanfaatan Film Dokumenter sebagai Pemenuhan Kebutuhan Informasi Sejarah di SD Islam Miftakhul Hikmah - Ayu, Dinda Muthiara (Nur Science Institute, 2025)
Learning history requires new learning methods so that students can properly receive the historical information or knowledge that has been given by the teacher to students. Learning history requires new learning methods because if history subjects are only explained using lectures from teachers, students will get bored. The use of documentary films is a new learning method provided by the Miftakhul Hikmah Islamic Elementary School teacher as a form of learning innovation so that students do not get bored and students can properly receive the information provided by the teacher. Researchers want to examine the usefulness of documentary films as a learning medium. This research uses qualitative research methods to obtain data, with data collection techniques in the form of interviews, observation and documentation. The results of this research are the existence of new learning methods and also how teachers obtain or can assess student abilities by providing evaluations to students.